An experimental investigation of the contribution of regular physical activity to organizational commitment of employees in a food company: The Contribution of Regular Physical Activity to Organizational Commitment of Employees in A Food Company - Dindar, Mustafa Deniz; Ozen, Gokmen (Progress in Nutrition, 2020)
Objective: Participation in regular physical exercise and sports activities has positive effects on physical and mental health. Organizational commitment is a very important factor affecting the productivity of employees in the business world. The purpose of this study is to investigate the contribution of participation in physical exercise and team sports activities on organizational commitment of employees. Methods: Ninety employees who have been working for a food production company for two years or more participated in this research. Participants grouped as control (CG), individual physical exercises (IPEG) and team sports activities (TSAG). IPEG participated in individual physical exercise programmes and TSAG groups participated in team sports activity programmes throughout eight weeks and two days in a week. Organizational Commitment Scale developed by Meyer, Allen and Smith (1993) and adopted to Turkish Culture and Turkish Language by Dağlı, Elçiçek and Han (2018) was used to determine the organizational commitment status of participants. Paired t-test and ANOVA test were used in the statistical analyses. Results: TSAG mean score was significantly higher than control group regarding organizational commitment total score means (p